Hubungan Pola Asuh Orang Tua dengan Tingkat Kemandirian Anak Usia Sekolah Di SDN Panjang Wetan 01 Pekalongan - Arif Purnomo Julianto (Universitas Pekalongan, 2010)
Background : A child to be independence have an opportunity, support and environtmental motivation and the environment, to reach autonomy for their self. Parenting as an important things to create the child independences.Methode : it was a descriptive correlation with approach of cross sectional, total sample in this research involved 59 student of class V in SDN Panjang wetan 01 Pekalongan in the year of 2007.Result : showed that 74,6% have democratic parenting method, 20,3% have parenting authority and 5,1% have permissive parenting method, 57,6% have good independence, 40,7% and 1,7% have less independence. This study indicates that parenting have relations with the degree of child independence.Key word : parenting, the degree of independence, school-age.